2010
DOI: 10.1007/s11356-010-0376-1
|View full text |Cite
|
Sign up to set email alerts
|

Status of feral oilseed rape in Europe: its minor role as a GM impurity and its potential as a reservoir of transgene persistence

Abstract: Feral oilseed rape is not a relevant source of macroscopic impurity at its present density in the landscape but provides opportunity for genetic recombination, stacking of transgenes and the evolution of genotypes that under strong selection pressure could increase and re-occupy fields to constitute an economic weed burden and impurity in future crops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 14 publications
1
78
1
2
Order By: Relevance
“…A 10-year survey (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), along road verges of a motorway revealed that most quadrats showed transient populations lasting one to four years (Crawley and Brown, 2004). These data and data from other demographic studies indicate a substantial turnover of populations of feral oilseed rape: only a small percentage of populations occurs at the same location over successive years, whereas the majority appears to die out rapidly (Crawley and Brown, 1995, 2004;Charters et al, 1999;Peltzer et al, 2008;Elling et al, 2009;Knispel and McLachlan, 2009;Nishizawa et al, 2009;Squire et al, 2011). However, if habitats are disturbed on a regular basis by anthropogenic activities such as mowing, herbicide applications or soil disturbance, or natural occurrences such as flooding, then feral populations can persist for longer periods (Claessen et al, 2005a;.…”
Section: Population Demography Of Feral Oilseed Rapementioning
confidence: 63%
See 4 more Smart Citations
“…A 10-year survey (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), along road verges of a motorway revealed that most quadrats showed transient populations lasting one to four years (Crawley and Brown, 2004). These data and data from other demographic studies indicate a substantial turnover of populations of feral oilseed rape: only a small percentage of populations occurs at the same location over successive years, whereas the majority appears to die out rapidly (Crawley and Brown, 1995, 2004;Charters et al, 1999;Peltzer et al, 2008;Elling et al, 2009;Knispel and McLachlan, 2009;Nishizawa et al, 2009;Squire et al, 2011). However, if habitats are disturbed on a regular basis by anthropogenic activities such as mowing, herbicide applications or soil disturbance, or natural occurrences such as flooding, then feral populations can persist for longer periods (Claessen et al, 2005a;.…”
Section: Population Demography Of Feral Oilseed Rapementioning
confidence: 63%
“…Demographic data on feral oilseed rape in different EU locations showed consistently that persistence in the soil seedbank allowed plants to recur after an absence of a year or more, while several populations persisted for two to four years (Squire et al, 2011). For the study site of Selommes, Pivard et al (2008a) estimated that up to 40% of the observed feral populations persisted mainly through seed emerging from the soil seedbank.…”
Section: Recruitment From Seed Emerging From the Soil Seedbank Or Fromentioning
confidence: 95%
See 3 more Smart Citations